Estudo das propriedades fotoluminescentes dos compósitos de MgMoO4:SrMoO4 e ZnWO4:CaWO4 obtidos pelo método de spray pirólise ultrassônico - Santiago, Anderson de Azevedo Gomes (2022)
Molybdates and tungstates are inorganic materials with immense potential in application as white light-emitting diodes (wLEDs), which are an alternative to traditional lighting sources. In this study, the synthesis and characterization of the composite MgMoO4:SrMoO4 (with molar ratios of 1:0; 0.75:0.25; 0.5:0.5; 0.25:0.75 and 0:1) and ZnWO4:CaWO4 (with molar ratios of 1:0; 0.8:0.2; 0.6:0.4; 0.4:0.6; 0.2:0.8 and 0:1), prepared by the ultrasonic spray pyrolysis method and their photoluminescent properties were investigated. Using X-ray diffraction, for MgMoO4:SrMoO4 samples, the monoclinic β- MgMoO4 phase was observed at a molar ratio of 1:0 and the tetragonal scheelite phase of SrMoO4 at a molar ratio of 0:1. However, for ZnWO4:CaWO4 samples, the monoclinic phase ZnWO4 was obtained at a molar ratio of 1:0 and the scheelite-type tetragonal phase of CaWO4 when the molar ratio was 0:1. The formation of a particulate material composed of both phases was observed for the intermediate molar ratios. Scanning electron microscopy images showed that MgMoO4:SrMoO4 and ZnWO4:CaWO4 particles show a spherical morphology formed by primary nanoparticles. Raman scattering spectroscopy allowed the precise identification of Raman modes for different compositions and their assignment to SrMoO4 or β-MgMoO4 and ZnWO4 or CaWO4 modes. Bandgap energies were found in a range between 4.2 eV and 4.4 eV for the MgMoO4:SrMoO4 samples and between 3.8 eV and 4.0 eV for ZnWO4:CaWO4, influenced by the order/disorder structural degree of the materials. The photoluminescence emission spectra of the particles showed neutral- and cool-white emission with high quality white light (CRI>80%). The MgMoO4:SrMoO4 samples synthesized with a molar ratio of 1:0, 0.25:0.75 and 0.5:0.5 formed materials with potential for application in LED lamps (6,500 K) and pure white light sources (5,500 K) while the samples of ZnWO4:CaWO4 can be considered as promising white light sources, mainly for the sample with molar ratio 0.2:0.8, for application in LED lamps (6,500 K).